Oral Presentations Abstracts: PROMOTING RESPONSIBLE RESEARCH PRACTICES BY TRAINING RESEARCHERS’ VIRTUES - INGUAGGIATO, Giulia; EVANS, Nathalie; STOLPER, Margreet; MOLEWIJK, Bert; WIDDERSHOVEN, Guy (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Promoting research integrity is crucial to achieve high quality and relevant results, and preserve public trust in science. In recent years, many codes of conducts, guidelines and regulations on national and international level, such as the European Code of Conduct for Research Integrity, have been issued to tackle this issue. However, these documents are often perceived as an externally imposed set of rules that researchers need to comply with in order to tick the box of integrity and get their research done. These research integrity efforts are important, but are they enough? We argue that in order to foster ‘good’ science, educating ‘good’ researchers is crucial. To respond to these issues, the VIRT2UE project has created an open source online training for researchers and educators that supports the internalization of the practices and principles of good science by building upon a virtue-based approach. Core elements of this approach are reflections on the intrinsic motivation of researchers and the cultivation of those moral characters which support the practices and principles of good science. The VIRT2UE training consists of a toolbox with training materials which can be used both online and offline, easy to use and adaptable to context. Starting from the assumption that virtues are learned through experience and by example, we will show what role trainers and educators can play in promoting a virtue-based approach to research integrity and what this implies for their own education and professionalization as trainers.